The Flash - Daley, John Francis 1985-; Wallfisch, Benjamin 1979-
Worlds collide when Barry uses his superpowers to travel back in time in order to change the events of the past. But when his attempt to save his family inadvertently alters the future, Barry becomes trapped in a reality in which General Zod has returned, threatening annihilation, and there are no Superheroes to turn to. That is, unless Barry can coax a very different Batman out of retirement and rescue an imprisoned Kryptonian, albeit not the one he's looking for. Ultimately, to save the world that he is in and return to the future that he knows, Barry's only hope is to race for his life. But will making the ultimate sacrifice be enough to reset the universe?
Spielfilm. USA. 2023
Keywords: Superheld; Actionfilm; Verfilmung; Flash / (Fictitious character) / Drama; Time travel / Drama; Good and evil / Drama; Superhero films; Time-travel films; Science fiction films; Action and adventure films; Feature films; Fiction films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Film; DVD-Video